SOURCES OF LOWER PALEOZOIC SANDSTONES FROM THE NORA-SUKHOTINO TERRANE: RESULTS OF U-Th-Pb AND Lu-Hf ISOTOPE STUDIES OF THE DETRITAL ZIRCONS - Y. V. Smirnov (Геодинамика и тектонофизика)
This paper presents the results of comprehensive geological and geochemical studies of sandstones from the Belaya basin of the Amur fragment of the Nora-Sukhotino terrane of the northeastern flank of South Mongolia-Khingan orogenic belt, as well as the results of isotopic (U-Th-Pb and Lu-Hf) studies of detrital zircons therefrom. The sandstones from the Belaya basin are characterized by significant variations in the composition of clastic material and major rock-forming elements, and by correspondence to arkoses and litharenites. They were accumulated due to erosion of geochemically mature felsic and intermediate igneous rocks. The sandstones are dominated by Ordovician, Cambrian, and Neoproterozoic zircons. The youngest zircons in sandstones from the Belaya basin are dated back to 451±8 Ma, with the lower age boundary set at the Late Ordovician. The Ordovician zircons, which have positive εHf(t) values and Early Paleozoic – Neoproterozoic Hf-model ages, could have been derived from island arc complexes. The Cambrian and Neoproterozoic zircon grains with positive εHf(t) values and Neo – Mesoproterozoic Hf-model ages could have been derived from Early Paleozoic and Neoproterozoic igneous rocks of the Bureya or Mamyn terranes. The available geological materials provide evidence that the sandstones from the Belaya basin are a fragment of the Early Paleozoic accretionary complex, which formed in the Early Paleozoic along the southeastern margin of the Mamyn (Xing’an) massif. However, a small amount of data on the Early Paleozoic and Neoproterozoic magmatism of the region hinders drawing more definite conclusions.